An investigation into linguistic features of verbs and their relation to the circumstances in the verbal processes in English and Vietnamese - Nguyễn Vũ Hoài Cúc (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This study aims to provide a relatively comprehensive description and analysis of the semantic and syntactic features of five typical verb groups and their circumstances in the verbal processes in English and Vietnamese. This study is expected to make a comparison of linguistic features of these verbs in English and Vietnamese and their relation to the circumstance; a classification of these verbs is hoped to do on functional basis